(untitled) (Journal of Hama University, 2024)
Spectrum analysis is an algorithm that estimates the strength of different frequency components (power spectrum) of a time domain cycle. This may also be called frequency domain analysis. The periodogram is one of the methods for estimating the spectral density. The spectrum is refined using spectral windows, by which we can detect the cycle of the time series. A group of spectral windows (Rectangular window, Triangular window or Barttlet window, Parzen window, Tukey window and Kaiser Window) was used to detect the cycle of time series by using MATLAB. Where the results showed that each of the rectangular window (Rectangular window) and Kaiser Window (Kaiser Window) are the windows that revealed all the roles, regardless of whether these roles are close or not. In addition, all the windows revealed all the divergent roles.